Reading with one eye closed? Or : what you miss when you do not read biblical texts multidimensionally - Jonker, Louis C. (Old Testament essays, 2006)
The methodological discussion between historical critics and textimmanent readers of the Old Testament is often articulated in terms of the distinction between synchrony and diachrony. Numerous scholars have shown in the debate that this distinction is artificial. Although one could distinguish between synchronic and diachronic perspectives, they cannot be separated. This paper is an attempt to take stock of how my own methodological thoughts have developed since the formulation of a multidimensional model in my dissertation (1993). I argue that our present methodological discussions should even go beyond the traditional distinction of synchrony and diachrony.